Excited state properties of Lanthanide(III) complexes with a nonadentate bispidine ligand - Abad Galan, Laura; Cieslik, Patrick; Comba, Peter; Gast, Michael; Maury, Olivier; Neupert, Lucca; Roux, Amandine; Wadepohl, Hubert (Chemistry - a European journal, 2021)
EuIII, TbIII, GdIII and YbIII complexes of the nonadentate bispidine derivative L2 (bispidine=3,7-diazabicyclo[3.3.1]nonane) were successfully synthesized and their emission properties studied. The X-ray crystallography reveals full encapsulation by the nonadentate ligand L2 that enforces to all LnIII cations a common highly symmetrical capped square antiprismatic (CSAPR) coordination geometry (pseudo C4v symmetry). The well-resolved identical emission spectra in solid state and in solution confirm equal structures in both media. As therefore expected, this results in long-lived excited states and high emission quantum yields ([EuIIIL2]+, H2O, 298 K, τ=1.51 ms, ϕ=0.35; [TbIIIL2]+, H2O, 298 K, τ=1.95 ms, ϕ=0.68). Together with the very high kinetic and thermodynamic stabilities, these complexes are a possible basis for interesting biological probes.
Gesehen am 14.04.2023